2014
DOI: 10.1002/jwmg.766
|View full text |Cite
|
Sign up to set email alerts
|

Northern bobwhite predator avoidance behavior in response to varying types of threat

Abstract: The flight behavior and cover use of northern bobwhite (Colinus virginianus) have been examined in several studies, but the current data lack quantitative measures of how bobwhites respond to natural threats. We examined aspects of bobwhite behavior in response to 4 threat categories: researcher, hunter, raptor, and mammal. We found that bobwhite flight distance is best predicted by threat type and covey size, and bobwhite flight speed is best predicted by threat type. Bobwhites flushed by the hunter threat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Decreased path tortuosity within the Reference treatment may be a product of the specific predator present, as predator type determines antipredator escape tactics (Perkins, Boal, Rollins, & Perez, 2014). Decreased path tortuosity within the Reference treatment may be a product of the specific predator present, as predator type determines antipredator escape tactics (Perkins, Boal, Rollins, & Perez, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased path tortuosity within the Reference treatment may be a product of the specific predator present, as predator type determines antipredator escape tactics (Perkins, Boal, Rollins, & Perez, 2014). Decreased path tortuosity within the Reference treatment may be a product of the specific predator present, as predator type determines antipredator escape tactics (Perkins, Boal, Rollins, & Perez, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has demonstrated an increase in bobwhite path tortuosity as a result of evading avian predators when compared to terrestrial threats, such as hunters (Perkins et al, 2014). Moreover, it has been suggested that Protean behavior is energetically costly and may only be utilized if prey are directly targeted by a predator (Jones et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This balance of strategies would limit the amount of visual exposure of prey to predators in both scenarios. In bobwhites, differences in anti‐predator behavior to threat type have been noted between raptors (aerial) and hunters (ground; Perkins et al ). Further, the influences of bobwhite anti‐predator behavior elicited in this study may exacerbate their exposure to natural predators.…”
Section: Discussionmentioning
confidence: 99%
“…, Perkins et al. ). Further research is therefore needed to assess the role of olfactory concealment in different cover types—such as wetlands, deserts, urban areas and croplands—and under predator assemblages comprised of an equal mix of visual and olfactory‐hunting species.…”
Section: Discussionmentioning
confidence: 99%
“…, Perkins et al. ). Because most terrestrial predator communities are dominated by species that use olfaction (hereafter olfactory predators) (Nams , Slotnick , Hughes et al.…”
Section: Introductionmentioning
confidence: 99%